The clinical and pathological features of plasma cell myeloma post solid organ transplantation. Issue 12 (17th September 2020) - Ofori, Kenneth; Soderquist, Craig R.; Murty, Vundavalli V.; Park, David; Vlad, George; Leeman‐Neill, Rebecca J.; Lentzsch, Suzanne; Alobeid, Bachir; Bhagat, Govind
Abstract: Plasma cell neoplasms (PCNs), comprising plasma cell myelomas (PCMs) and plasmacytomas, which occur after solid organ transplantation, represent rare subtypes of monomorphic post‐transplant lymphoproliferative disorders (M‐PTLDs). Data regarding the clinical and pathological features of post‐transplant (PT)‐PCMs are limited. To gain a better understanding of disease biology, we performed comprehensive immunophenotypic analysis, reviewed cytogenetic analysis results and evaluated clinical outcomes of PT‐PCMs diagnosed and treated at our institution. Fifteen PT‐PCM (M: F ‐ 4:1) and two PT‐MGUS (two males) cases were identified. The median age of PT‐PCM patients was 68 years (29‐79 years) and PCMs presented at a median of 9.7 years (0.5‐24.7 years) after transplantation. The PT‐PCMs accounted for 11.6% of all M‐PTLDs and the period prevalence was 9/3108 (0.29%), 3/1071 (0.28%), 2/1345 (0.15%) and 1/878 (0.11%) post kidney, heart, liver and lung transplantation. Lytic bone disease was observed in 1/11 (9%) patients. Marrow plasma cell infiltration ranged from 10%‐70% (median 20%), with 10/15 (67%) and 5/15 (33%) cases manifesting immature and plasmablastic morphology. The immunophenotype of all cases and cytogenetic abnormalities, identified in 60% of cases, were similar to multiple myeloma (MM) of immunocompetent individuals. All PT‐PCMs were EBER negative. Ten of 11 (91%) patients with active MM were treated, all with proteasome inhibitor‐based therapy. Treatment response and 5‐year overall survival (54.5%) was comparable to MM of immunocompetent individuals. However, the survival of patients with plasmablastic PCMs was inferior to those with immature PCMs. 0ur findings indicate PT‐PCMs to be predominantly late onset PTLDs that have similar clinicopathologic characteristics as conventional MM.